2013
DOI: 10.2337/db12-1745
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Krüppel-Like Factor 3 (KLF3/BKLF) Leads to Upregulation of the Insulin-Sensitizing Factor Adipolin (FAM132A/CTRP12/C1qdc2)

Abstract: Krüppel-like factor 3 (KLF3) is a transcriptional regulator that we have shown to be involved in the regulation of adipogenesis in vitro. Here, we report that KLF3-null mice are lean and protected from diet-induced obesity and glucose intolerance. On a chow diet, plasma levels of leptin are decreased, and adiponectin is increased. Despite significant reductions in body weight and adiposity, wild-type and knockout animals show equivalent energy intake, expenditure, and excretion. To investigate the molecular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…37,95,96 Importantly, they demonstrate that the FAM132A promoter is bound and regulated in vivo by KLF3 and show that in Klf3 −/− mice, adipolin levels are significantly elevated. 37 Interestingly, KLF3 recruits the NAD + /NADH-dependent metabolic sensor C-terminal binding protein to regulate gene expression, suggesting a possible mechanism allowing this pathway to respond to metabolic stimuli and energy levels intracellularly. 97,98 While the extent to which the KLF3-adipolin pathway underlies the favorable metabolic phenotype of KLF3 null mice remains to be fully resolved, this discovery provides novel therapeutic potential, perhaps via targeting of signaling molecules that regulate KLF3 activity.…”
Section: Leptinmentioning
confidence: 99%
See 3 more Smart Citations
“…37,95,96 Importantly, they demonstrate that the FAM132A promoter is bound and regulated in vivo by KLF3 and show that in Klf3 −/− mice, adipolin levels are significantly elevated. 37 Interestingly, KLF3 recruits the NAD + /NADH-dependent metabolic sensor C-terminal binding protein to regulate gene expression, suggesting a possible mechanism allowing this pathway to respond to metabolic stimuli and energy levels intracellularly. 97,98 While the extent to which the KLF3-adipolin pathway underlies the favorable metabolic phenotype of KLF3 null mice remains to be fully resolved, this discovery provides novel therapeutic potential, perhaps via targeting of signaling molecules that regulate KLF3 activity.…”
Section: Leptinmentioning
confidence: 99%
“…However, in a recent study, Bell-Anderson et al have elucidated a novel regulatory pathway controlling FAM132A gene expression. 37 In this, and previous work, they describe how mice deficient in the transcriptional repressor Krüppel-like Factor 3 (KLF3/BKLF) are lean due to reduced adiposity, and also demonstrate that loss of KLF3 leads to a favorable metabolic phenotype on a high fat diet, associated with resistance to obesity, improved insulin sensitivity and glucose tolerance. 37,95,96 Importantly, they demonstrate that the FAM132A promoter is bound and regulated in vivo by KLF3 and show that in Klf3 −/− mice, adipolin levels are significantly elevated.…”
Section: Leptinmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there are significantly lower concentrations of full-length and total (full-length and globular) adipolin in diet-induced obese mice, leading to an increase in the ratio of globular:full-length adipolin, possibly through upregulation of furin in adipose tissue (Enomoto et al 2012). In addition, genetic studies in mice have shown that the loss of Krüppel-like factor 3 leads to upregulation of adipolin (Bell-Anderson et al 2013); on the other hand, loss of Krüppel-like factor 15 resulted in a decrease in adipolin levels (Enomoto et al 2013).…”
Section: Introductionmentioning
confidence: 99%